Developing a rule-driven clinical decision support system with an extensive and adaptative architecture - Hederman, Lucy (IEEE, 2012)
Clinical guidelines are central to the implementation of clinical decision support systems (CDSSs). Addition or revision of clinical guidelines usually causes the (re-) development of new or existing CDSSs. The separate maintenance of clinical knowledge and their driving systems implies extra system development cost and low knowledge delivery efficiency. We propose, in this paper, an approach to liaise the two activities and support a complete knowledge-driven CDSS architecture. It will accommodate and disseminate new knowledge with minimum efforts required to make relevant changes to the systems, but make use of the new knowledge whenever it becomes available. A Multi-Agent System architecture and a rule-based knowledge repository are put together to realize this goal.
IEEE 14th International Conference one-Health Networking, Applications and Services
PUBLISHED
Keywords: Clinical decision support system; Clinical guideline; Evidence-based medicine; Model-Driven Architecture; Multi-Agent System; Rule-based knowledge modelling; Health informatics; Medical Informatics